Metabolics-Based Study on the Therapeutic Mechanism Behind the Effect of Shenhuang Plaster Applied to the Shenque Acupoint on Gastrointestinal Motility in POI Mice - Yanan Shi; Chenglei Wu; Ting Liu; Rongyun Wang; Bin Ding; Qiuhua Sun (Metabolites)
Background: Postoperative ileus (POI) is a common postoperative clinical complication that significantly affects postoperative rehabilitation and quality of life in patients and can even produce secondary complications, leading to serious consequences. External treatment using Shenhuang Plaster (SHP) (Shenque acupoint administration) has definite effects and unique advantages in the prevention and treatment of POI, but its mechanism is not completely clear. In this study, we investigated the therapeutic mechanism behind the effect of Shenhuang Plaster applied to the Shenque acupoint on gastrointestinal motility in POI mice based on metabolomics. Materials and Methods: C57BL/6 mice were divided into three groups: blank control (Ctrl), model (POI), and intervention (POI + SHP) groups. SHP treatment was started 3 days before modeling. We employed several behavioral tests and gastrointestinal transit function measurements and performed qRT-PCR analysis, 16S rRNA gene sequencing, and metabolomics analysis on serum metabolites. Results: We found that SHP could reduce the mRNA expression of inflammatory mediators in the smooth muscle tissue of the small intestine, regulate the structure and function of the intestinal microbiota, and modulate serum phenylalanine, carnitine, and glutamic acid levels. Conclusions: POI mice had obvious intestinal flora disorders and metabolic disorders of amino acids and their derivatives, and there was a significant correlation between differential flora and differential metabolites. SHP could effectively regulate the concentration of intestinal flora and serum metabolites and the metabolic pathway related to amino acids in vivo and, ultimately, achieve a therapeutic purpose in POI. In this study, it was found, for the first time, that applying SHP to the Shenque acupoint could effectively regulate the serum metabolites of phenylalanine, carnitine, and glutamate, and improve postoperative intestinal motile disturbance through association with the intestinal flora.